Smallholder farming commercialization and food security in Malawi: do land rights and intrahousehold bargaining power matter? - Laston Petro Manja; David Eddings Zingwe; Alexious E.S. Kamangila (Agriculture & Food Security)
Abstract Background The role of agricultural commercialization in improving household food security has been widely documented. Convinced of its importance, in 2020, the Government of Malawi adopted agricultural productivity and commercialization as one of its three key pillars in the pursuit of Agenda 2063. Nonetheless, the importance of institutions in this nexus remains understudied. In this paper, we investigate the role of the interaction of engendered land rights regimes and intrahousehold bargaining power in dictating the agricultural commercialization–food security nexus in a male-dominated society of Malawi. First, we examine the effect of engendered land rights regimes and spouse bargaining power on commercialization of smallholder farming. Then, we analyze the effect of commercialization on food security factoring in the role of land rights regimes and intrahousehold power. We use round 5 of the Malawi Integrated Household Survey (IHS5) fielded in 2019/2020, employing various econometric models such as the fractional logit and Tobit. We control for endogeneity by employing a control function technique. Results The study results show that households under a matrilineal land holding regime are less likely to commercialize and that an increase in spouse bargaining power increases the likelihood of commercialization. We also find spouse bargaining power to be instrumental in improving food security, especially for households under a matrilineal land holding regime. Interestingly, we find that an increase in commercialization is likely to improve food security for households under a matrilineal land holding regime if there is more spousal bargaining power. Conclusions Effective policy formulation and implementation around issues of agricultural commercialization and food security requires a fair understanding of the dynamics at play both within households and across different traditions. The results indicate that collaborative decision-making between the household head and spouse holds significant importance in the maximization of food-security-returns from commercialization. This is especially true for matrilineal societies.